Diverse Enzymological Patterns of Phenylalanine Biosynthesis in Pseudomonads Are Conserved in Parallel with Deoxyribonucleic Acid Homology Groupings - Whitaker, Robert J. (1981)
l-Tyrosine biosynthesis in nature has proven to be an exceedingly diverse gestalt of variable biochemical routing, cofactor specificity of pathway dehydrogenases, and regulation. A detailed analysis of this enzymological patterning of l-tyrosine biosynthesis formed a basis for the clean separation of five taxa among species currently named Pseudomonas, Xanthomonas, or Alcaligenes (Byng et al., J. Bacteriol. 144:247-257, 1980). These groupings paralleled taxa established independently by ribosomal ribonucleic acid/deoxyribonucleic acid (DNA) homology relationships. It was later found that the distinctive allosteric control of 3-deoxy-d-arabino-heptulosonate 7-phosphate synthase in group V, a group dominated by most named species of Xanthomonas (Whitaker et al., J. Bacteriol. 145:752-759, 1981), was the most striking and convenient criterion of group V identity. Diversity in the biochemical routing of l-phenylalanine biosynthesis and regulation was also found, and phenylalanine patterning is in fact the best single enzymatic indicator of group IV (Pseudomonas diminuta and Pseudomonas vesicularis) identity. Enzymological patterning of l-phenylalanine biosynthesis allowed discrimination of still finer groupings consistently paralleling that achieved by the criterion of DNA/DNA hybridization. Accordingly, the five ribosomal ribonucleic acid/DNA homology groups further separate into eight DNA homology subgroups and into nine subgroups based upon phenylalanine pathway enzyme profiling. (Although both fluorescent and nonfluorescent species of group I pseudomonads fall into a common DNA homology group, fluorescent species were distinct from nonfluorescent species in our analysis.) Hence, phenylalanine patterning data provide a relatively fine-tuned probe of hierarchical level. The combined application of these various enzymological characterizations, feasibly carried out in crude extracts, offers a comprehensive and reliable definition of 11 pseudomonad subgroups, 2 of them being represented by species of Alcaligenes.